Evaluations of biopesticides for the management of food legume aphids and pod bores in Morocco - Kemal, Seid Ahmed; Boulamtat, Rachid (2023)
Different Aphid species (Acyrthosiphon pisum and Aphis fabae) and pod borers are key production constraints on faba bean, field pea, chickpea and lentil in south Asia, north Africa and East Africa. Besides direct economic damage, some aphid species play important roles as vectors of legume viruses like Pea seed-borne mosaic virus (PSbMV). Sources of resistance to aphids and pod borers is not available in temperate food legumes and farmers largely use insecticides to protect their crops. Looking for biopesticides against aphids and pod borers is an important area of research to develop biorational pest management in food legumes.